CONDITIONS OF ROLES AND DUTIES DIVISION IN RURAL HOUSEHOLDS - Zwierzyk, Justyna; Żelazna, Krystyna (Acta Scientiarum Polonorum. Oeconomia, 2005)
The main assumption of this elaboration is to recognize the work division in households and farms and the decision process among rural families. Obtained results indicate that men are responsible for running farms whereas women field of activity is limited to production work and running households. Few respondents, according to the poll, change the traditional work division system into the partnership model. Among rural inhabitants the tendency has been revealed that they implement modern technical and organizational solutions to improve their work.